Do prato ao reconhecimento público: o menu das confrarias gastronómicas - Cunha, Luís (Trabalhos de Antropologia e Etnologia, 2020)
The gastronomic confraternities are a little studied reality, both in gastronomy and in relation to debates on heritage and tourism. In this work, we tried to look at this universe from two different registers. On the one hand, considering the general panorama of the gastronomic confraternity’s movement, listing and distinguishing the confraternities that formalized the inscription in federative instances. On the other hand, trying to attend to the dynamics of the different confraternities, as reflected in the magazine Nona Arte, digital publication created by the Portuguese Federation of Gastronomic Confraternities. As we shall see, issues such as the relationship between tradition and innovation or the debates around the heritage/tourism binomial, find in the world of gastronomic confraternities a relevant expression and that it is important to know.